Improving Mathematics Learning Outcomes Through the Use of Animated Video Media in Learning to Build Flat Grouping for Mentally Impaired Students - Usman Jayadi; Riinawati Riinawati; Kasim Sahreen (Lafadz Jaya Publisher, 2022)
The use of media can increase students' enthusiasm and interest in learning. This study shows that learning mathematics with the use of model media has a positive impact on improving student learning outcomes. Based on data analysis, the learning outcomes of students in the teaching and learning process using Animation Video Media in each cycle have increased. This has a positive impact on student learning outcomes, which can be shown by increasing the average value of students in each cycle which continues to increase. Thus, it can be concluded that the animated video media is suitable to be applied to learning to recognize the elements of flat shapes for mentally retarded students.